Penatalaksanaan Fisioterapi dengan Modalitas Short Wave Diathermy dan Codman Pendulum Exercise pada Kasus Frozen Shoulder Dextra - Ellya Febri Nurhazira; Wanti Hasmar; Indah Permata Sari (3031-8572, 2022)
Frozen shoulder is an aetiological condition characterized by significant limitation of active and passive motion of the shoulder that occurs due to deep tissue damage. In addition, a frozen shoulder is described as a shoulder condition characterized by pain and limited range of motion (ROM). Frozen shoulder occurs when the joint capsule that surrounds the shoulder joint becomes shriveled and forms scar tissue, a condition known as shoulder adhesive capsulitis. To find out the physiotherapy management for frozen shoulder dextra by using short wave diathermy and codman pendulum exercise modalities to reduce pain and increase joint range of motion. After performing physiotherapy four times with short wave diathermy and codman pendulum exercise modalities, the result showed a decrease in pain and increase in joint motion. short wave diathermy and codman pendulum exercise can reduce pain and increase joint range of motion.